The Realization of Affect, Judgement, and Appreciation of Discoursal Attitude in Library Ghost Webtoon - Eka Kurniawati; Sri Wuli Fitriati; Suwandi Suwandi (English Education Journal, 2023)
This research is aimed to evaluate and interpret the meaning of feelings into the webtoon makers to readers through a written. This research was qualitative since the findings took the form primarily of words. The source is a Webtoon. The researchers chose a Webtoon because interested in examining Appraisals using Webtoon because it can be media in learning and teaching for educators and will also help them improve their reading skills; the author is curious about the realization of Attitudinal in the Webtoon, especially on Library Ghost Webtoon. The reason for choosing this study is because Attitudes are believed to affect the meaning of language directly. Attitude plays an essential role in the expression of interpersonal meanings of language. The instruments applied were Library Ghost, adapted by Webtoon to assess the attitude system and the appraisal resources checklist to determine the distribution of appraising items of attitude in Webtoon and the relationship of the attitude system on Webtoon. This study proves that a text such as a webtoon, especially Library Ghost, has three items of attitude system in each episode. The author of this webtoon is more dominant in using affect than appreciation and judgment in the webtoon. This study shows that writing in a text can express the emotions or feelings contained in the text. Because Webtoon is a conversation-based online comic. Therefore, affect is more dominant than appreciation and judgment. In the ghost webtoon library, the author expresses more emotions and feelings to the characters.